Penerapan Risk-Based Audit terhadap Siklus Persediaan oleh KAP X (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the application of Risk-Based Audit (RBA) in examining the inventory cycle at Public Accounting Firm (KAP) X. Inventory was chosen as the primary focus because it is an account with a high risk of material misstatement in financial statements, due to the complexity of management such as variations in item types, differing recording methods, and potential impairment. The risk-based audit approach is essential to enable auditors to allocate resources efficiently to high-risk areas, thereby producing more reliable audit opinions. This research employs a qualitative descriptive method, with data collected through in-depth interviews with senior auditors who have direct experience in inventory audits. The interviews focused on auditors’ strategies for identifying high-risk areas, responses to significant findings, and challenges encountered during the audit process. The results show that auditors apply RBA by prioritizing expired inventory, non-moving items, and discrepancies between physical counts and administrative records. Audit procedures include physical observation, tracing the flow of goods, confirming supporting documents, and evaluating client recording methods. Implementing RBA enhances audit effectiveness and efficiency by focusing on genuinely high-risk areas. However, auditors face technical challenges, such as damaged labels, limited physical access to warehouses, clients’ lack of attention to inactive items, and limited inventory movement data, requiring additional procedures to achieve sufficient assurance. This study confirms that applying RBA in the inventory cycle plays a strategic role in minimizing the risk of material misstatement, improving audit quality, and providing practical insights into the challenges auditors face in real-world implementation.